If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 7x + -5 Reorder the terms: 12 = -5 + 7x Solving 12 = -5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 12 + -7x = -5 + 7x + -7x Combine like terms: 7x + -7x = 0 12 + -7x = -5 + 0 12 + -7x = -5 Add '-12' to each side of the equation. 12 + -12 + -7x = -5 + -12 Combine like terms: 12 + -12 = 0 0 + -7x = -5 + -12 -7x = -5 + -12 Combine like terms: -5 + -12 = -17 -7x = -17 Divide each side by '-7'. x = 2.428571429 Simplifying x = 2.428571429
| (X+9)(x+9)=12 | | 117c-13-14=115c+13 | | (10+6)/2 | | 10m-4m=8m-8 | | 8/4/1/2 | | 4x+12=6x+60 | | -1+2(-5r-6)=-83 | | (x-8)=9 | | 4x-y=3y+7,x+8y=4 | | 4x+12=6x-60 | | -3+b=4 | | -5v+3(v+6)=26 | | -3n=3 | | 9x-24=10x | | (9x+8)(8+x)=(x+5)(9x+8) | | 142+x=3x+64 | | 10+6/2 | | 20x-22y=58 | | 5/3p^2-3/p | | (x+5)(x-5)=(x+1)(x+3)+12 | | 4/20(2x-15)+12/20x=45/20 | | 4x^1/4-17x^1/2+4=0 | | 4=n+11 | | 3x-4=x+9 | | 2(4-3x)+12=7x-5(2x-7) | | -3(8k-3)=-17+2k | | 7(x-1)+3= | | 2(x-2)/3+5x=10 | | 3w-5+3w-5= | | 2(x-2)/5+5x=10 | | 240/275 | | 4x-(x^2)=0 |